Improved photosynthetic characteristics of Chlorella mutant MS700 induced by nuclear radiation. (December 2020) - Lu, Hongxiang; Cheng, Jun; Wang, Zhenyi; Zhu, Yanxia; Zhang, Xiangdong; Liu, Jianzhong
Graphical abstract: Highlights: Chlorella mutant MS700 had a higher carbon fixation efficiency than the wild type. MS700 had a 104.2% higher chlorophyll-based flash oxygen yield. MS700 had a more efficient downstream process pulling electrons in PQ pool. MS700 had a 27.7% higher capability of incorporating its dissolved inorganic carbon. Abstract: Chlorophyll a variable fluorescence and oxygen evolution were measured in microalgae Chlorella and its mutant MS700, which was mutated by nuclear radiation with an increased biomass yield. The mutant MS700 showed an improvement in photosynthetic characteristics under various CO2 concentrations. Results showed that chlorophyll-based flash oxygen yield was 104% higher in MS700 than in the wild type, indicating more available electron acceptors in the plastoquinone pool and a higher light to chemical energy conversion efficiency. The higher chlorophyll a variable fluorescence at the end of PQ pool-regulated phase implied a more robust mechanism for consumption of electrons generated in PSII, indicating a more efficient downstream process. Monitoring of CO2 fixation in the Calvin cycle showed that the mutant had a 27.7% higher capability of incorporating its dissolved inorganic carbon. The oxygen evolution rate was 31.4% higher in MS700, which also indicated a higher CO2 fixation rate. These results consistently demonstrated carbon fixation efficiency in the mutant MS700, resulting in the higher biomass yield.